CONDITIONS FOR THE USE OF CATALYSTS IN THE LIQUID PHASE (Spectrum Journal of Innovation, Reforms and Development, 2022)
The purpose of this study is to develop methods for the synthesis of a number of pyrrol and its derivatives under normal conditions on the basis of commercially available raw materials in the presence of homogeneous catalysts.